2018
DOI: 10.3389/fphar.2018.00120
|View full text |Cite
|
Sign up to set email alerts
|

Is Excessive Polypharmacy a Transient or Persistent Phenomenon? A Nationwide Cohort Study in Taiwan

Abstract: Objectives: Target populations with persistent polypharmacy should be identified prior to implementing strategies against inappropriate medication use, yet limited information regarding such populations is available. The main objectives were to explore the trends of excessive polypharmacy, whether transient or persistent, at the individual level. The secondary objectives were to identify the factors associated with persistently excessive polypharmacy and to estimate the probabilities for repeatedly excessive p… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

2
19
0

Year Published

2018
2018
2023
2023

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 14 publications
(21 citation statements)
references
References 38 publications
2
19
0
Order By: Relevance
“…The majority of people in our study experienced sustained exposure to a large number of medicines over time. While few studies have explored temporal changes in polypharmacy, our findings are consistent with population‐based studies of older adults in Sweden and Taiwan that found the majority (74%) of older adults exposed to 5 or more medicines sustained this exposure over the subsequent year, 15 and 2/3 (67%) of people with exposure to 10+ medicines had repeat period of exposure to 10+ medicines within a year 17 …”
Section: Discussionsupporting
confidence: 88%
See 1 more Smart Citation
“…The majority of people in our study experienced sustained exposure to a large number of medicines over time. While few studies have explored temporal changes in polypharmacy, our findings are consistent with population‐based studies of older adults in Sweden and Taiwan that found the majority (74%) of older adults exposed to 5 or more medicines sustained this exposure over the subsequent year, 15 and 2/3 (67%) of people with exposure to 10+ medicines had repeat period of exposure to 10+ medicines within a year 17 …”
Section: Discussionsupporting
confidence: 88%
“…Most of the extant research quantifying polypharmacy report cross‐sectional or annual trends in estimates of prevalence 9–13 . The few studies that have explored polypharmacy longitudinally have examined duration of exposure to polypharmacy, or time to repeat polypharmacy episodes 15,17 . Little is known about how the number of medicines and the nature of medicine use change for patients over time—which is needed to understand the types of common patient journeys (e.g.…”
Section: Introductionmentioning
confidence: 99%
“…These two dimensions, the intensity and the composition of polypharmacy, are important. However, only few studies have made a distinction between chronic and transient polypharmacy . Our study shows that exposure to polypharmacy is not always stable over time and that transient polypharmacy episodes are not uncommon.…”
Section: Discussionmentioning
confidence: 62%
“…Hospitalization in the previous year was identified through the question: “Did you stay in the hospital last year?” Polypharmacy was defined as taking five or more medications [ 10 , 39 ].…”
Section: Methodsmentioning
confidence: 99%